2010
DOI: 10.1016/j.jare.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of applying static electric field on the physical parameters and dynamics of laser-induced plasma

Abstract: In order to improve the performance of the LIBS technique -in particular its sensitivity, reproducibility and limit of detection -we studied the effect of applying a static electric field with different polarities on the emission spectra obtained in a typical LIBS set-up. The physical parameters of the laserinduced plasma, namely the electron density N e and the plasma temperature T e , were studied under such circumstances. In addition to the spectroscopic analysis of the plasma plume emission, the laser-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…A comparison of the spectral line intensities of Cu I 570.02 nm, 578.21 nm, measured with the external electric field (49 V mm −1 ) and without the external electric field, is shown in figure 5, which reveals an eight-fold signal intensity enhancement in the Cu I line at 570.02 nm in the presence of the external electric field. The signal intensity enhancement measured in the presence of the external electric field is in good agreement with earlier reports [28,29]. As the distance between the electrodes is only 3 mm, it will be hard to ignore the contribution of cavity confinement effects [32].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A comparison of the spectral line intensities of Cu I 570.02 nm, 578.21 nm, measured with the external electric field (49 V mm −1 ) and without the external electric field, is shown in figure 5, which reveals an eight-fold signal intensity enhancement in the Cu I line at 570.02 nm in the presence of the external electric field. The signal intensity enhancement measured in the presence of the external electric field is in good agreement with earlier reports [28,29]. As the distance between the electrodes is only 3 mm, it will be hard to ignore the contribution of cavity confinement effects [32].…”
Section: Resultssupporting
confidence: 90%
“…Further, the plasma temperature remains the same in the spark-dischargeassisted LIBS and in the conventional LIBS. The effect of the static electric field on the laser-generated plasma [28] showed signal intensity enhancement along with a small decrease in the electron number density, while the plasma temperature remains the same. In a recent article [29], a low voltage and high current arc discharge technique, coupled with LIBS, yields an increased persistence time of the plasma plume, along with the signal intensity enhancement.…”
Section: Introductionmentioning
confidence: 95%
“…It is known from the previously investigations that plasma generation is influenced by the laser parameters (intensity, pulse duration, and wavelength) [10][11][12][13][14][15][16][17][18][19][20][21][22], the physical properties of target material (ionization potential, reflectivity and thermal conductivity), and the ambient conditions [23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They found that, for all the layered specimens of Au and Ag grown onto Cu substrates, as the working distance (difference between the lens-to-sample distance and the focal length of the lens) increases, the intersection point value between the two layered materials increases, while both the average ablation rate and crater depth are decreasing [18]. Elhassan et al [19] demonstrated the effect of applied electric field on plasma parameters and LIBS signal emitted. They used pure aluminum impeded in one of two copper electrodes.…”
Section: Factors Affecting Libsmentioning
confidence: 99%
“…On the other hand, the electron number density was found to decrease slightly in the case of forward biasing, with a much stronger decrease (about one order of magnitude) in the case of reversed biasing. They found that signal-to-noise (S/N) ratio and the limit of detection (LOD) were improved in case of forward biasing electric field [19]. Electric field was found to have no effect on laser-induced shock wave (SW) velocity, which depends mainly on the laser parameters, such as pulse energy and spot size.…”
Section: Factors Affecting Libsmentioning
confidence: 99%